DISCOVERY IN FIVE FUNDAMENTAL ANGLES AT THE SUBATOMIC LEVEL PLUS A THREE-DIMENSIONAL BODY - Poramest Boonsri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
After having proved time values matching numbers in all number lines (xt, yt, zt), time as a vector, law of directions of time, time-fields, and discovery of the polarity of gravitational force, we tried to find deeply fundamental angles inside the three-dimensional body as the objective of this study. Numbers, time values matching the numbers, eight resultant directions of time in eight parts, six resultant directions of six time-fields in a threedimensional body were used to be data. Vector was used to prove angles in a threedimensional body. The investigation found five kinds of fundamental angles as follows: (1) four angles as 180o , (2) 12 angles as 109.4712o , (3) 12 angles as 70.5287o , (4) 24 Magic angles as 54.7356o , and (5) 24 dihedral angles as 125.264o . The benefits of this study show that time can explain gravity in the world of the celestials and the Magic angle at the subatomic level in one coherent picture. It may lead us to control energy from a threedimensional body, especially at the subatomic level. Besides, it is warning economists the second time to realize that there is something wrong about theoretical economics time. The conclusion is also trying to develop economics as a new branch of science with an open system entirely in the final.